PENERAPAN TRANSPARANSI DAN AKUNTABILITAS DALAM PENGELOLAAN PENCAIRAN DANA MUAT DI PT YUDHISTIRA PERKASA ABADI - Putri, Nabila Dwi; Safira, Selma Putri (Universitas Nusa Cendana, 2025)
This study examines the implementation of transparency and accountability principles in the management of loading fund disbursement at PT Yudhistira Perkasa Abadi. The objective of the research is to analyze how transparency and accountability are applied in the company’s financial disbursement procedures. The study uses a descriptive qualitative method, with data collected through observation and interviews. The findings reveal that transparency is implemented through open access to information, systematic documentation, and the involvement of multiple parties in the verification and authorization process. Meanwhile, accountability is demonstrated through clear divisions of responsibility, the use of official documents such as vouchers and Disbursement Notes (NPD), and orderly transaction recording. The loading fund disbursement mechanism in place supports a professional, organized, and trustworthy financial management practice.